2007
DOI: 10.1097/bot.0b013e31802c5b51
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of 109 Tibial Plateau Fractures: Five- to 27-Year Follow-up Results

Abstract: Long-term results after open reduction and internal fixation for tibial plateau fractures are excellent, independent of the patient's age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
211
2
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(240 citation statements)
references
References 32 publications
9
211
2
12
Order By: Relevance
“…There is a consensus that treatment of these soft tissue pathologies is needed to obtain a stable knee joint, achieve good functional results, and prevent development of osteoarthritis [9]. However, in this study, the mean follow-up time was 2.7 years (range, 1.2 -3.6 years), therefore, development of osteoarthritis could not have been monitored.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…There is a consensus that treatment of these soft tissue pathologies is needed to obtain a stable knee joint, achieve good functional results, and prevent development of osteoarthritis [9]. However, in this study, the mean follow-up time was 2.7 years (range, 1.2 -3.6 years), therefore, development of osteoarthritis could not have been monitored.…”
Section: Discussionmentioning
confidence: 73%
“…Surely, a stable knee is essential for the postoperative immediate motion, restoration of former knee function and reducing risk of secondary osteoarthritis in long term [9]. Many authors reported the advantage of early knee joint ROM after surgical treatment of tibial plateau fracture [1]- [3] [7]- [9] [11]- [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rademakers et al performed examinations at one year and an average of 14 years after operated TPF and concluded that the one year FU adequately predicts long-term results. [8] However, these studies did not address longitudinal changes in radiological OA in individual patients. A longer FU may provide more information about the development of OA after TPF.…”
Section: Introductionmentioning
confidence: 99%